Analisis Kinerja Keuangan KSU Sri Nadi Bersama Sebelum dan Selama Masa Pandemi Covid 19 di Kota Denpasar, Bali - GUNAWAN, GUFRAN RIZALDY DANANG; DEWI, RATNA KOMALA; DJELANTIK, A.A. AYU WULANDIRA SAWITRI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
Analysis of Financial Performance of KSU Sri Nadi Bersama Before and During the Covid 19 Pandemic The concept of creating shared value is a business sustainability practice that has the nature to provide strengthening and independence of the surrounding environment. This consensus has been implemented by cooperatives in accordance with its function that gathers weak economic strength to become the lifeblood of the economy and strengthen the economic life of the nation. However, the Covid 19 pandemic has proven to have a bad effect on the micro to maceoeconomics. Therefore, this study aims to analyze the financial performance of KSU Sri Nadi Bersama Denpasar before and during the Covid 19 pandemic. The study used primary data in the form of monthly financial statements and primary data through interviews. The data analysis techniques used are descriptive analysis and paired t test on financial performance liquidity ratio, solvency ratio, profitability ratio and activity ratio. The results showed that there was a significant difference in liquidity ratio and solvency ratio in the pre-Covid 19 pandemic when compared to during the Covid 19 outbreak. Profitability ratios and activity ratios that showed no significant difference in financial performance in the period before and during the Covid 19 outbreak.